The Relationship between Age, Education and Occupation ANC Visits for Primigravida Pregnant Women at the Sragen Health Center - Anya Cahya Melati; Kusuma Estu Werdani (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Maternal health programs in Indonesia are struggling to reduce the Maternal Mortality Rate (MMR). Even though ANC services have increased, visit coverage has fluctuated. A preliminary study in Sragen Regency highlights the need to explore the relationship between age, education and employment with ANC visits among primigravida. This study aims to determine the relationship between age, education and employment with ANC visits among primigravida pregnant women at the Sragen Community Health Center, Central Java. This research is a quantitative study with a cross-sectional design. The research was conducted in October 2023 at the Sragen Community Health Center, Sragen Regency with a population of 100 primigravida pregnant women who visited ANC from January to August 2023. The sample collection technique was total sampling so that the research sample was 84 pregnant women. The research instrument used a questionnaire. Analysis of research data using bivariate analysis of the Chi-Square test processed with SPSS version 20. The research results showed that the majority of the 84 primigravida pregnant women studied at the Sragen Community Health Center were aged 20 to 35 years (90.5%), with a bachelor's education level (47.6%), and were not working (66.7%). There is no relationship between age (p-value=0.683), there is a relationship between education level (p-value=0.014), and there is a relationship between employment (p-value=0.040) and ANC visits by primigravida pregnant women at the Sragen Community Health Center. It is hoped that pregnant women will look for sources of information about the importance of ANC visits for pregnant women in order to learn and improve or increase their knowledge about ANC Services in order to reduce maternal mortality rates. Keywords: ANC, Mortality Rate, Primigravida